Александровский сад: [роман] / Алексей Пиманов, Борис Яновский - Пиманов Алексей Викторович (АиФ-Принт, 2006)
Экземпляры: аб. (2012) / Инвентарный номер: 54903 / Цена: 63.21 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 32 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44